Application of quantum dot gate nonvolatile memory (QDNVM) in image segmentation. Issue 3 (March 2016) - Karmakar, Supriya; Gogna, Mukesh; Jain, Faquir
Abstract This paper presents the application of quantum dot gate nonvolatile memory (QDNVM) in image processing application. The charge accumulation in the gate region varies the threshold voltage of QDNVM, which can be used as a reference voltage source in a comparator circuit. A simplified comparator circuit can be implemented using the QDNVM. In this work, the use of QDNVM-based comparators in image processing specially image segmentation is demonstrated, which can be efficient in future image processing application.